Studi Kasus Profil Diagnostik Terapi Wicara Pada Klien Gagap Usia 27 Tahun - Ilham Akerda Edyyul; Rahmi Khalida; Yuli Afmi Ropita Sari (JURNAL KESEHATAN MERCUSUAR, 2023)
One of the disruptions in fluency is the lack of smoothness in speech that does not correspond to the speaker's age, and this lack of smoothness affects the rhythm and average number of words produced when speaking. This research aims to identify disruptions in fluency rhythm experienced by a 27-year-old client with stuttering. The research method employed is a case study (qualitative descriptive). The research implementation in this case begins with observation, client interviews, and testing, including reading, storytelling, and two-way communication tests. The results of this study conclude that the client's diagnosis is beginning stuttering accompanied by secondary stuttering behaviors such as eye movements, movements downward, hand clenching, and toe tapping. The client also exhibits a feeling of fear and moderate to severe anxiety, with the ICD-10 code for stuttering being F98.5. Stuttering syndromes include core behaviors such as stoppages, repetitions, and prolongations. The total stuttering index for the client during reading is 8.9%, during storytelling is 15.06%, and during two-way communication is 10.28%. Based on the data assessment, the author suggests reducing stuttering by strengthening the client's modalities, such as fostering a strong desire to learn, parental support for the client's recovery, and motivation from the client to reduce stuttering.